1996
DOI: 10.1111/j.1440-1746.1996.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HLA alleles in Japanese patients with cirrhosis due to chronic hepatitis C

Abstract: Hepatitis C virus (HCV) leads to chronic liver disease in at least 50-60% of infected people and approximately 40-50% of these patients will go on to develop cirrhosis due to chronic hepatitis C (HCV-C). The pathogenic mechanisms that result in HCV-C are unknown. Sixty Japanese patients with HCV-C were examined for HLA-A, B, C and DR alleles by serologic typing and for HLA-DQB1 alleles by DNA typing using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. As the control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…The associations between HLA Class I antigens and the outcome of HCV infection are extensively investigated in different ethnic populations such as Caucasian Americans and populations from Korea, Italy, Russia, Spain, Ireland, Saudi Arabia, Western India, Japan and Germany [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The earlier reported associations showed ethnic and geographical differences sometimes with contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between HLA Class I antigens and the outcome of HCV infection are extensively investigated in different ethnic populations such as Caucasian Americans and populations from Korea, Italy, Russia, Spain, Ireland, Saudi Arabia, Western India, Japan and Germany [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The earlier reported associations showed ethnic and geographical differences sometimes with contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…In a German study, DRB1*1302, which is associated with slower disease progression, 19,21 was shown to have decreased frequency in HCV-infected individuals compared with controls. 27 DR4 and DQB1*0401 were more frequent in Japanese HCVinfected subjects compared with random controls, 26 and in a Japanese study of progression, both of these alleles are associated with more rapid progression. 62 A comparison of results in each of the three outcomes presents a wide array of HLA alleles that are associated with HCV infection.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Several studies have attempted to examine susceptibility to HCV infection by comparing HLA alleles in individuals who are anti-HCV-positive with either the general population or with people who are anti-HCVnegative (Table 4). [25][26][27][28][29]31,[63][64][65] Because the assumption cannot be made that the general population has been exposed to HCV, true associations may be missed by this experimental design. In addition, identification of individuals who have been exposed to HCV but remain seronegative is difficult.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
See 2 more Smart Citations